2004
DOI: 10.1093/intimm/dxh115
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic 'linker region' in Toll-like receptor 3 controls receptor localization and signaling

Abstract: Toll-like receptor 3 (TLR3) recognizes double-stranded RNA and transmits signals to activate NF-kappaB and the interferon (IFN)-beta promoter via the newly identified adaptor, TICAM-1. The extracellular LRR domain of TLR3 is engaged in the ligand recognition, while the intracellular TIR domain is crucial for the adaptor binding and signal transduction upon ligand stimulation. Here, we analyzed TLR3 localization in human monocyte-derived immature dendritic cells (iDCs) and stable transfectants expressing human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 44 publications
6
117
0
Order By: Relevance
“…We amplified 22 cycles for β-actin, and 32 cycles for other genes. M, 1-7 stands for DNA marker (DL2000), zygote, dome, shield, 1-somite, prim-5, protruding mouth, and adult stages, respectively Funami et al 2004;Sarkar et al 2003), and the TIR domain might be considered as a cassette (Xu et al 2000). Most of the conserved residues were located in the hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We amplified 22 cycles for β-actin, and 32 cycles for other genes. M, 1-7 stands for DNA marker (DL2000), zygote, dome, shield, 1-somite, prim-5, protruding mouth, and adult stages, respectively Funami et al 2004;Sarkar et al 2003), and the TIR domain might be considered as a cassette (Xu et al 2000). Most of the conserved residues were located in the hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
“…The TIR domain of GrTLR3s was short of two β-sheets and two helices, which caused the hydrophobic core to be exposed outside. Funami et al (2004) identified three amino acid residues essential for ligand-inducing NF-κB and IFN-β promoter activation (Phe 732 , Leu 742 , and Gly 743 ) in human TLR3, all of which were present in the GrTLR3 sequence (Phe 734 , Leu 744 , and Gly 745 ). Sarkar et al (2003) identified specific tyrosine residues in the TIR domain as being essential for the intracellular signaling in human TLR3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, TLR3, TLR7, TLR8, and TLR9 have been shown to be expressed in intracellular fractions, such as endosomes (Heil et al, 2003;Matsumoto et al, 2003;Latz et al, 2004). It has been reported that TLR3-, TLR7-, or TLR9-mediated recognition of their ligands requires endosomal maturation (Heil et al, 2004;Funami et al, 2004). Whether the TLR is on or in the cell, studies have shown that either phagosomal/lysosomal or endosomal/ lysomal compartments may be the main sites for TLR recognition of microbial components (Latz et al, 2004;Leifer et al, 2004;Underhill et al, 1999).…”
Section: Tlrs and Their Sub-cellular Locationmentioning
confidence: 99%
“…In general, TLRs are represented by an extracellular N-terminus with a leucine-rich repeat region (LRR) and a conserved cytoplasmic C-terminus with a Toll-interleukin-1 receptor (TIR) domain (Matsushima et al, 2007). The TIR-conserved amino acid regions have been shown to be implicated in the signaling and localization of TLRs (Sarkar et al, 2003;Funami et al, 2004), while the LRR has been implicated in pathogen detection (Bell et al, 2003). TLR family components are expressed by cells of the immune system and specialized cells, such as neutrophils, macrophages, dendritic cells, vascular endothelial cells, and intestinal epithelial cells (Skjaeveland et al, 2008).…”
Section: Introductionmentioning
confidence: 99%